(untitled) (UNED Research Journal, 2017)
Groups of hawksbill sea turtles have been observed over the years, close to the coast of the Marino Ballena National Park. For this reason, in February 2015, we monitored its coast to identify aggregation sites. Turtle size estimates, and identification, were done by direct observation by the divers and from the boat. From February to December 2015, fourteen monitor records per sampling point were done and 41 turtles were recorded. They were 30cm - 80cm long and 59% of the individuals aggregated in one sample point. Five genera of sponges were registered as potential food: Haliclona sp, Spirastrella sp, Mycale sp, Aplyscina sp and Axinella sp and one tunicate, Rhopalaea birkelandi. The E. imbricata population was mainly composed of juveniles, and the turtles were found in zones where they have not been previously reported.